2016
DOI: 10.1097/psy.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Cortisol Exposure and Declarative Verbal Memory

Abstract: Objective Exposure to endogenous cortisol is associated with hippocampal degeneration and may contribute to problems with declarative memory, but effects of persistent vs. phasic cortisol elevations have not been established. The present longitudinal investigation examined persistent individual differences and phasic changes in cortisol as they related to verbal memory, executive functions, and subjective cognitive function. Methods Older adults (N = 132, aged 60 to 93 years) were followed for up to 5 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…8,31 Furthermore, the affective stress of chronic pain may be, as other stressful exposures are, 33,34 implicated in faster cognitive decline via putative cortisol-based pathways. 35,36 If these mechanisms fully explain the accelerated cognitive decline we demonstrate here, resolution of pain would mitigate the detrimental cognitive effects. Classic studies do describe cognitive improvement after initiation of opioid treatment, though these studies were not performed in an elderly population.…”
Section: Discussionmentioning
confidence: 77%
“…8,31 Furthermore, the affective stress of chronic pain may be, as other stressful exposures are, 33,34 implicated in faster cognitive decline via putative cortisol-based pathways. 35,36 If these mechanisms fully explain the accelerated cognitive decline we demonstrate here, resolution of pain would mitigate the detrimental cognitive effects. Classic studies do describe cognitive improvement after initiation of opioid treatment, though these studies were not performed in an elderly population.…”
Section: Discussionmentioning
confidence: 77%
“…et al, 2008; Ouanes et al, 2017a; Sang et al, 2018). Likewise, most (Beluche et al, 2010; Geerlings et al, 2015; Segerstrom et al, 2016; Ouanes et al, 2017a,b; Echouffo-Tcheugui et al, 2018), even though not all (Lee B.K. et al, 2008) studies exploring the relationship between episodic memory and cortisol levels have found an association between elevated cortisol and poorer episodic memory among older adults without dementia.…”
Section: Glucocorticoid Receptors and Cortisol Effects On Cognitionmentioning
confidence: 99%
“…Possibly due to lack of power, the current study may not have observed an effect of cortisol on memory, but future work with larger sample sizes could ascertain whether moderated (age) mediation (HPA-axis functioning) is present. Further, longitudinal evidence indicates that persistent elevated daily cortisol exposure is a better predictor of memory in healthy older adults than single measurements alone (Segerstrom et al, 2016). Antidepressant use in a portion of our sample (n = 22; ~58%) may also contribute to these null results, a notable limitation of the design as it related to the current investigation.…”
Section: Discussionmentioning
confidence: 78%